Comparison of Oral Isotretinoin vs Azithromycin in the Treatment of Acne Vulgaris - Alaa Sh. Abdulbari; Noor M. Ali; Ahmed R. Abu Raghif; Nadheer A. Matloob (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Acne vulgaris is a chronic inflammatory disease of the pilosebaceous follicles, common inadolescents, characterized by comedones, papules, pustules, cysts, nodules, and occasionally scars. Thisstudy was designed to compare multi B vitamins, folic acid and homocysteine levels in patients withmoderate to severe acne vulgaris with those of the apparently healthy control group and to investigate theeffect of isotretinoin and azithromycin treatments on these biochemical parameters and comparison betweentwo drugs.Methods: This study was conducted on sixty women patients with acne and thirty as a control group. Thepatients were allocated into two groups, A and B, group A was given 500 mg of azithromycin taken onalternative days for 3 months and group B was given 40mg/day isotretinoin for 3 months.Results: The study showed significant differences (p<0.05) in serum levels of vitamins B6, B7, B12 andfolic acid, while no significant difference in serum homocysteine in patient group when compared to controlgroup. The results showed significant positive correlation between serum vitamins and clinical score andsignificant difference were detected in both group when compared between pre and post treatment.Conclusions: The results indicate higher pre-treatment vitamin B12 levels, versus the control group andpositive correlation between clinical score and vitamin B12, support the assertion that vitamin B12 playsa role in the etiopathogenesis of acne vulgaris. Both azithromycin and isotretinoin were effective in acnetreatment but azithromycin has less side effects.